New Insights on the Role of N6-Methyladenosine RNA Methylation in the Physiology and Pathology of the Nervous System - Dermentzaki, Georgia; Lotti, Francesco (Frontiers in Molecular Biosciences, 2020)
RNA modifications termed epitranscriptomics represent an additional layer of gene regulation similar to epigenetic mechanisms operating on DNA. The dynamic nature and the increasing number of RNA modifications offer new opportunities for a rapid fine-tuning of gene expression in response to specific environmental cues. In cooperation with a diverse and versatile set of effector proteins that “recognize” them, these RNA modifications have the ability to mediate and control diverse fundamental cellular functions, such as pre-mRNA splicing, nuclear transport, stability, and translation. N6-methyladenosine (m6A) is the most abundant of these RNA modifications, particularly in the nervous system, where recent studies have highlighted it as an important post-transcriptional regulator of physiological functions from development to synaptic plasticity, learning and memory. Here we review recent findings surrounding the role of m6A modification in regulating physiological responses of the nervous system and we discuss its emerging role in pathological conditions such as neuropsychiatric and neurodegenerative disorders.